A comparative study of retail banking practices in compliance with regulatory standard. Issue 3 (2nd July 2019) - Mittal, Suman; Garg, Krishan K.; Aggarwal, Renu
Abstract : Purpose: The Indian banking industry has undergone many changes with the advent of changing economic environment in the country. Many changes have taken place in terms of customer services, work culture, infrastructure, approach to sales and customer relationship management amongst others. This paper aims to attempt to evaluate the adherence of BCSBI code by the banks. Customer perception has been evaluated to analyse the adherence of the code. Also, the authors have tried to evaluate the impact of customer type (mass and class customers) and bank type (based on bank ownership- private and public banks) on the compliance of the code by the bankers or minimum regulatory requirements with respect to customer services. Questionnaire has been developed as per the Banking Code and Standard Board of India (a customer services cell of Reserve Bank of India), and BCSBI has been used as a regulatory standard to compare the level of compliance by the banks. Design/methodology/approach: Primary data have been collected from private and public sector banks. In the first step, instrument validity and reliability has been checked by using structural equation modelling; in the second step, descriptive statistics has been used to know the extent of fulfillment of standard by banks; and in the third step, a two-way multivariate analysis of variances has been used to do the comparative analyses of the respondents data. Findings: The overall finding of the research shows that overall adherence of the dimension of code are not in sync with the objective of the code. Study also has shown the mindset of the Indian bankers that how they predominantly serve the class customers and push those products to the customers which are target based or earn profitability for the banks and incentives for the banker. Private banks are ahead in compliance with respect to the customer services, but they are also ahead in sales malpractices. Practical implications: This study is an eye opener for the regulators, as per BCSBI regulations, surprise supervision take place every year, but this study shows the ineffectiveness of that supervision. Following the BCSBI norms by the banks is just eyewash of regulators, but all the norms are fulfilled only in papers but not in actual practice. Originality/value: The research paper is original piece of work; the researcher did not find any study related to BCSBI code in Indian as well as in international literature.